In Vitro Dissolution Enhancement of Curcumin by Melt Dispersion and Solvent Casting Technique Aided by Molecular Modelling Approach - Anindya Jana; Subrata Kumar Biswal; Rudra Narayan Sahoo; Partha Niyogi; Subrata Mallick; Rajaram Mohapatra (Journal of Global Pharma Technology, 2021)
Purpose: The oral bioavailability of curcumin is low due to its lipophilic nature. The drug also tends to degrade in alkaline pH. This inherent character of curcumin limits its stability and oral bioavailability. Use of polymeric carriers to alter the physicochemical nature of the drug is one of the favoured techniques of drug formulation. Aim of this study was to improve the in-vitro dissolution and solubility of curcumin by using hydrophilic carriers such as polyethylene glycol (PEG) and polyvinylpyrrolidone (PVP) of different grades and to check the effect of the different excipients used in the formulation of curcumin by solid dispersion technique. Methods: Solid dispersions of curcumin have been prepared by the solvent evaporation and melting method by using carriers in suitable ratios. In this experiment, ethanol was used as an organic solvent for solvent evaporation. The presence of different release rate modifiers such as croscacamellose sodium, kollidon CL and sodium and lauryl sulphate (SLS) in the SD formulation were also studied. In-silico approach has been applied to quantify the curcumin and carrier interaction. Results: The solubility of the solid dispersion prepared by the solvent evaporation and the melting method was found to be 13.5 and 78.9 fold to that of the pure curcumin respectively. Physical characterization by FTIR and DSC studies advocated that the physical state of crystalline drug has been modified in solid dispersions due to its dispersion in the polymer matrix. Conclusion: Dissolution studies revealed that all the formulations were having better drug release profile compared to the physical mixture. The lowering of binding energy in in-silico ducking study indicated towards possible molecular drug carrier interaction. Keywords: Curcumin, Solubility, Dissolution, Solid dispersion.